Clinical outcome in patients monitored by the NIHSS after mechanical thrombectomy in relation to time and cerebrovascular risk factors - Mileusnić, Valentina; Grkić, Irena; Zečević, Aleksandra (Vojnosanitetski pregled, 2024)
Background/Aim. Mechanical thrombectomy (MT) is an endovascular treatment that involves the extraction of thrombotic masses in the first hours of acute ischemic stroke (AIS) from the large blood vessels of the head and/or neck. The aim of the study was to determine the role of predictors (time and vascular risk factors) of the clinical outcome of patients with AIS monitored by the National Institute of Health Stroke Scale (NIHSS). Methods. The study included 134 patients diagnosed with occlusion of a blood vessel of the head and/or neck with a clinical picture of AIS who met the criteria for MT and in whom, upon admission to the hospital, existing vascular risk factors were observed. In relation to the time parameter from the onset of the clinical picture of AIS to the start of MT, the patients were divided into two groups. The first, the examined group, consisted of 85 (63.4%) patients in whom recanalization was initiated within the first four hours from the onset of symptoms, and the second, the control group, consisted of 49 (36.6%) patients in whom recanalization was initiated after the fourth hour. The results were monitored by the change of the NIHSS score at the time of discharge of the patient, on the 30th and 90th day, in relation to the NIHSS score on admission. Results. There was no statistically significant difference between the groups except for the variables endovascular treatment (EVT) and previous vascular event [cardiovascular disease (CVD)] (p
Keywords: endovascular procedures; ischemic stroke; risk factors; time-to-treatment; treatment outcome.